THE USE OF THE KANSEI ENGINEERING METHOD IN THE DESIGN OF THE MULTIVARIANCE MOUNT WEAPON WIRELESS CONTROL SYSTEM - Prayit Suprayitno; Marsono Panjaitan; Khusnul Ain; Moh. Yasin (The Republic of Indonesia Defense University, 2022)
The Frogman Forces Command or Kopaska (Komando Pasukan Katak) is one of the special forces owned by the Indonesian Navy (TNI AL). Kopaska unit often carries out covert operations such as Amphibious Operations, Special Operations, and other supports to expedite Indonesian Navy operations. To support the implementation of these tasks, the Kopaska unit needs to be equipped with special equipment to carry out operational tasks. Currently, the Kopaska unit does not yet have a weapon mount that can be controlled remotely. This study proposes a multivariance weapon wireless system control that is designed to be used remotely by using a mobile application through the internet. A Multivariance Mount Weapon Wireless System Control was designed using the Kansei Engineering method to provide alternative tools to support Kopaska tasks more effectively and efficiently and be able to minimize material and personnel losses. The average value of the level of user satisfaction with the tool design has reached a fairly good position, namely 3.17 from the initial value of 1.36 (scale 1 to 4), so this new product is ready as an alternative to be produced.Â